KEABSAHAN NIKAH SIRI DALAM PERSPEKTIF MASLAHAH - Wahyudani, Zulham (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, dan Ekonomi Islam, 2020)
This study focus on exploring maslahah of the marriage registration for nikah siri. Based on the result, first; the goverment used maslahah approacj to determine the marriage registration as one of the marriage requirements. therefore, the unregistered marriages will be punished as the illegal one. Nowdays, the marriage registration had become the publication to justify the legality of someone's marriage, as well as to protect their right and obligation such as the protection of their offspring, property, life and so on. second, marriage registration cannot be negotiated to be undone by providing legal certainty through the revision of law No. 1 of 1974. This study recomended that every nikah siri should be register to the KUA to obtain their marriage legality from the government.